TDRD7 participates in lens development and spermiogenesis by mediating autophagosome maturation. Issue 11 (2nd November 2021) - Tu, Chaofeng; Li, Haiyu; Liu, Xuyang; Wang, Ying; Li, Wei; Meng, Lanlan; Wang, Weili; Li, Yong; Li, Dongyan; Du, Juan; Lu, Guangxiu; Lin, Ge; et al.
ABSTRACT: In humans, TDRD7 (tudor domain containing 7) mutations lead to a syndrome combining congenital cataracts (CCs) and non-obstructive azoospermia (NOA), characterized by abnormal lens development and spermiogenesis. However, the molecular mechanism underlying TDRD7's functions in eye and testicular development are still largely unknown. Here, we show that the depletion of this gene in mice and humans resulted in the accumulation of autophagosomes and the disruption of macroautophagic/autophagic flux. The disrupted autophagic flux in tdrd7- deficient mouse embryonic fibroblasts (MEFs) was caused by a failure of autophagosome fusion with lysosomes. Furthermore, transcriptome analysis and biochemical assays showed that TDRD7 might directly bind to Tbc1d20 mRNAs and downregulate its expression, which is a key regulator of autophagosome maturation, resulting in the disruption of autophagosome maturation. In addition, we provide evidence to show that TDRD7-mediated autophagosome maturation maintains lens transparency by facilitating the removal of damaged proteins and organelles from lens fiber cells and the biogenesis of acrosome. Altogether, our results showed that TDRD7 plays an essential role in the maturation of autophagosomes and that tdrd7 deletion results in eye defects and testicular abnormalities in mice, implicating disrupted autophagy might be the mechanism that contributes to lens development and spermiogenesis defects in human. Abbreviations : CB: chromatoid bodies; CC: congenital cataract; CTSD: cathepsin D; DMSO: dimethyl sulfoxide; LAMP1: lysosomal-associated membrane protein 1; LECs: lens epithelial cells; MAP1LC3/LC3/Atg8: microtubule-associated protein 1 light chain 3; MEFs: mouse embryonic fibroblasts; NOA: non-obstructive azoospermia; OFZ: organelle-free zone; RG: RNA granules; SQSTM1/p62: sequestosome 1; TBC1D20: TBC1 domain family member 20; TDRD7: tudor domain containing 7; TEM: transmission electron microscopy; WT: wild type.